The Influence of Financial Secrecy and National Culture toward Tax Compliance - Ari Kristanto; Christina Kusumadewi (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2022)
Tax compliance is essential to pursue the fulfillment of countries’ tax revenue. This research aims to prove the effect of country level of financial secrecy and the resraint culture toward the tax compliance behavior. We expect that the financial secrecy would reduce the tax compliance. Furthermore, we also hypothesize that the restraint culture in a society influences tax compliance negatively. This research uses control variables i.e: democracy, tax rate, and law enforcement. By using cross-countries data of 62 countries processed by multiple regression analysis, it is concluded that financial secrecy has a negative influence toward tax compliance. Moreover, the restraint culture does not implied to have any effect on tax compliance. The findings of this research provide additional contribution as an empirical study in a global scale about the influence of financial secrecy and restraint culture on tax compliance. Based on the result, it can be recommended the government that should promote transparency in the financial sector to minimize non-compliant behavior.